Aborsi dalam Etika Kristen - Silva Silva; Siska Wira Sasmitha; Sarmauli Sarmauli (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Abortion is a controversial issue that involves debates across various sectors, including legal, religious, ethical, and health aspects. Defined as the termination of pregnancy before the fetus can survive outside the womb, abortion in Indonesia is regulated by Health Law No. 36 of 2009, Article 75, which allows the procedure only in cases of medical emergencies and pregnancies resulting from rape. Despite these regulations, illegal abortions still occur frequently, driven by unwanted pregnancies, economic issues, and social stigma. This paper will discuss various aspects, including the causes of abortion, health impacts, types of abortion in special cases, and the Christian ethical perspective. The research method employed is literature review. The findings indicate that abortion can occur due to various factors such as fear, health issues, socio-economic conditions, and misunderstandings about its consequences. Illegal abortions pose serious risks to women's physical and mental health, including infections, bleeding, emotional trauma, and even death. Medically, abortion may be performed to protect the mother’s life in high-risk pregnancies, such as in cases of uterine cancer or rape. However, from the Christian ethical perspective, abortion is viewed as contrary to God's will, as the fetus is considered a living being that must be protected from conception.